Konseling Individual Dengan Pendekatan Realita Dalam Mengembangkan Sikap Percaya Diri Siswa SMP Negeri 8 Denpasar - Irfan Ramdhoni; Putu Agus Semara Putra Giri (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this research is to find out that Individual Counseling with a Reality Approach can Develop Self-Confidence in Students at SMP Negeri 8 Denpasar. This research was planned for 2 cycles, each cycle with 1 meeting. This research uses a cyclical classroom action research design. This effort is made to foster students' courage and enthusiasm because essentially a feeling of lack of self-confidence is born because of feelings of fear, whether it is fear of failure or because they are not confident in their abilities and all of this is the influence of the wrong mindset. The results of the research show that the results of services for students at SMP Negeri 8 Denpasar in cycle 1 to increase self-confidence using the Behavior Contract obtained an average score for cycle 1 of 68.0 with the highest score being 90, there were 4 people and the lowest score was 70, there were 11 people. Meanwhile, in cycle II, the average score for cycle II was 79.0, with the highest score being 90, there were 7 people and the lowest score was 70, there were 8 people. Students who did not complete both in cycle I and cycle II were the same students, this was because these students basically had no intention of learning. Based on data on student learning outcomes from cycle I and cycle II, it showed that there was an increase in student learning outcomes at SMP Negeri 8 Denpasar shows the results of increasing compliance with self-confidence using Behavioral Contracts. Individual Counseling with a Reality Approach can Increase the Self-Confidence of Students at SMP Negeri 8 Denpasar.